Pengaruh Komitmen Organisasi, Kompensasi, dan Lingkungan Kerja terhadap Kinerja Karyawan PT Schlumberger Geophysics Nusantara Jakarta - Farizka Sitta Pratiwi; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
Any company of any kind of business, requires human resources who have the ability to think, act and be skilled in the face of business competition. For that, the company is required to improve the quality of resources resulting in increased employee performance and at the same time can contribute to the improvement of company performance. As an International based company, employees of PT Schlumberger Geophysics Nusantara Jakarta IT Analyst in serving their customers are required to perform well. But from the performance data obtained, employee performance cycle of IT Analyst fluctuate. Therefore, this study aims to determine the positive influence between organizational commitment, compensation and work environment on employee performance.Sample in this research is employee of IT Analyst section amounted to 30 with census method. Data collection method in this research is with questionnaire. This research was conducted by using multiple linear regression analysis and simple. The result of research shows that there is positive and significant influence between each variable of organizational commitment to employee performance, and there is influence and significant between work environment variable to employee performance and there is negative and not significant influence between variable of compensation to employee performance.Suggestions from researchers is the company must be able to maintain the commitment of employees and the work environment by way of bonding among employees. In addition, the company must also pay attention to bonus rations provided by employees, especially the IT analysts, can be transferred through additional facilities - facilities provided for employees.